Intercalation and Adsorption of Organic Dyes on Layered Double Hydroxides - Abd Aziz, Azira (2003)
Nanostructured material of layered organic-inorganic hybrid nanocomposites can be generated by encapsulation of an organic moiety into an inorganic lamellar in which the open lamellar systems such as layered double hydroxides (LDHs) can be used as the host for this study, synthesis of nanocomposite materials was carried out by using Mg/Al LDH as a host of inorganic layers and naphthol blue black (NEB), fast green (FG) and methyl orange (MO), organic dyes, as a guest It was found that the concentrations of the organic moiety and pH are critical for the formation of the well-ordered nanolayered hybrid materials The optimum concentration of NBB at 1 50 x 10-³ M, FG of 250 x 10⁻² M and 300 x 10² M of MO at pH 10 resulted a well-ordered nanolayered organic-inorganic hybrid nanocomposites FTIR spectrum of each nanocomposites resembled a mixture of each spectrum of the organic and inorganic species, indicating the presence of both in the resulting materials Surface morphology of Mg/AI-LDH and its nanocomposites show agglomerates of compact and non-porous structure, a typical surface morphology for LDH and Its nanocomposites.